Techno-economic Analysis on the Production of Zinc Sulfide Nanoparticles by Microwave Irradiation Method - Azizah Nurdiana; Lydzikri Astuti; Rismaya Pramesti Dewi; Risti Ragadhita; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (ASEAN Journal of Science and Engineering, 2022)
Zinc sulfide is a semiconductor that is widely used in various fields. Synthesis of zinc sulfide nanoparticles by microwave irradiation method has promising prospects because of its advantages, such as commercially available precursors, short reaction times, low operating temperatures, and produced high quantity and high-quality products. The purpose of this study was to evaluate the feasibility of the production of zinc sulfide from zinc nitrate hexahydrate and thioacetamide by microwave irradiation method. The evaluation was done from the engineering and economic perspectives. The feasibility analysis method from the engineering perspective was done by designing the initial production design on a large scale, whereas the analysis from an economic perspective was done by calculating various economic parameters (i.e., Gross Profit Margin, Cumulative Net Present Value, Internal Rate Return, Payback Period, Break Event Point, and Profitability Index). The engineering perspective showed that the production of zinc sulfide nanoparticles can be done on a large scale due to the commercial availability of materials and tools. Based on the economic evaluation, this project is ideal for an industrial scale. The profits increased over 20 years and the payback period was achieved within two years. We hope this study can provide references to readers, industry, and researchers regarding the feasibility analysis of the production of zinc sulfide nanoparticles by microwave irradiation method on a large scale.